Data Sheet 5_Morphological and phenological shifts in semiarid grasses paralleled climate and land use changes.csv - Julio César da Silva (22679243) (2025)
Plants respond to climate change through shifts in traits such as height, leaf width, and flowering time. However, little is known about how grass species in semiarid ecosystems are responding. In this study, we tested three hypotheses: (1) grass species are experiencing shifts in their vegetative and reproductive organs through time, (2) precipitation is the primary driver of these morphological shifts, and (3) the reproductive period of annual grasses changes through years in the Brazilian semiarid region. We analyzed morphological and phenological data from 590 herbarium specimens of four annual grass species collected between 1859 and 2022, along with climate data from 1960 onwards. Using simple and multiple linear regressions, we assessed relationships between morphological, phenological, climatic, and temporal variables. We tested changes in phenological synchronicity related to two periods of land use alterations. Our results revealed morphological changes throughout 1859-2022: three species showed reductions in plant height, two species exhibited shorter leaves and inflorescences, and one species presented smaller spikelets. Phenological times were delayed with increasing temperatures, although no consistent directional change in reproductive phenology was observed over the last 163 years. We also found a reduction in phenological synchronicity correlated with increasing land use shift. These findings contribute to understanding morphological and phenological shifts of grasses from semiarid ecosystems in parallel to climate and land use changes.